2022
DOI: 10.3389/fped.2022.852903
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Aicardi-Goutières Syndrome Type 6 and Dyschromatosis Symmetrica Hereditaria With Congenital Heart Disease and Mitral Valve Calcification – Phenotypic Variants Caused by Adenosine Deaminase Acting on the RNA 1 Gene Homozygous Mutations

Abstract: Dyschromatosis symmetrica hereditaria (DSH), characterized by a mixture of hyper- and hypopigmented macules on the skin, is a rare pigmentary dermatosis of autosomal dominant inheritance. The pathogenic gene is adenosine deaminase acting on the RNA 1 gene (ADAR1), mutations in this gene also lead to Aicardi-Goutières syndrome type 6 (AGS 6), a rare hereditary encephalopathy with isolated spastic paraplegia. The pathomechanism of the ADAR1 gene mutations inducing DSH has not been clarified yet. We report the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Lesions arise in infancy or early childhood and tend to increase in number until adolescence. Concurrent presentation of DSH and AGS 6 has been previously described with compound heterozygous and homozygous ADAR mutations 1–3 . Our case reports on a patient with de novo, heterozygous ADAR variants associated with DSH and AGS 6.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Lesions arise in infancy or early childhood and tend to increase in number until adolescence. Concurrent presentation of DSH and AGS 6 has been previously described with compound heterozygous and homozygous ADAR mutations 1–3 . Our case reports on a patient with de novo, heterozygous ADAR variants associated with DSH and AGS 6.…”
Section: Discussionmentioning
confidence: 52%
“…Concurrent presentation of DSH and AGS 6 has been previously described with compound heterozygous and homozygous ADAR mutations. [1][2][3] Our case reports on a patient with de novo, heterozygous ADAR variants associated with DSH and AGS 6. However, we cannot exclude the possibility of another unknown mutated allele in the non-coding region of ADAR is responsible for the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…29 Dyschromatosis symmetrica hereditaria (DSH), a rare autosomal dominant hereditary pigmented skin disorder, may arise in patients with AGS6 type. 30 AGS also has clinical manifestations of liver, kidney and other organs. [31][32][33][34][35] These suggest that we should consider AGS when the aforementioned 'atypical' phenotypes appear.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Alburaiky et al found a phenotypic association between Opsoclonus‐myoclonus syndrome and AGS 29 . Dyschromatosis symmetrica hereditaria (DSH), a rare autosomal dominant hereditary pigmented skin disorder, may arise in patients with AGS6 type 30 . AGS also has clinical manifestations of liver, kidney and other organs 31–35 .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Liu et al reported the first Chinese case of dyschromatosis symmetrica hereditaria with Aicardi-Goutières syndrome caused by A homozygous mutation of the ADAR1 gene (c.1622T>A). In cardiac terms, the patient had significant cardiac involvement, patent ductus arteriosus, VSD, and symptoms of progressive heart failure ( Liu et al, 2022 ). It may be related to the mutation site located in the protein domain of ADAR1 gene ( Liu et al, 2022 ).…”
Section: Adar1 In Cvdsmentioning
confidence: 99%